SEPARATION OF MIXTURES By COMBINING RECTIFICATION AND FRACTIONAL CRySTALLIZATION PROCESSES - G. A. Nosov; M. V. Mikhailov; A. I. Absattarov (Тонкие химические технологии)
Various options of separation of binary mixtures by combining the processes of fractional crystallization and rectification are considered. The base mixture, depending on its composition, can be initially directed to the rectification stage or to one of the stages of separated components crystallization using the proposed variants. The flow diagrams of integrated heat exchanging systems and schemes involving open and closed type heat pumps under consideration for the determination of ways of reducing energy consumption of the coupled processes were suggested. These solutions enable improving the processes energy efficiency. In addition, the analysis of the effect of the composition and temperature of the initial mixture, the temperature of fractionation at the crystallization stage, the composition of distillates and bottom products on the separation parameters was carried out. It was found that when the initial mixture is fed to the stage of crystallization of one of the components, the energy costs for carrying out the process under consideration are usually lower than when the initial mixture is fed to the rectification stage. It is shown that using a combination of fractional crystallization and rectification processes can significantly expand the possible separation range and improve the technical and economic characteristics of the separation process.